1996
DOI: 10.1111/j.1365-2575.1996.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Formalized systems development methodologies: a critical perspective

Abstract: Systems development issues occupy a position of central importance in the information systems field and much has been prescribed in the quest for successful systems developmenf. However, given the well-documented 'software crisis', success is far from guaranteed for systems development projects. Many researchers see the solution to the software crisis in terms of increased control and the more widespread adoption of rigorous and formalized system development methodologies. This paper presents some arguments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(17 citation statements)
references
References 40 publications
(51 reference statements)
0
17
0
Order By: Relevance
“…Method engineering is the systematic discipline of designing, constructing and adapting ISD methods (Kumar & Welke, 1992), and is primarily focused on the relationship between methodologies and methods (Brinkkemper, 1995;Iivari et al, 2000). There is empirical evidence that method engineering has already had impact on methods, if informally, as existing research on method use in practice has consistently found that information systems methods, as far as they are used, are applied adaptively, customized to fit the organization and project in question without regard for the tools' consistency or appropriateness with the methodology involved (Wynekoop & Russo, 1993;Hardy et al, 1995;Chatzoglou & Macaulay, 1996;Fitzgerald, 1996). Situational method engineering assumes that the developer can obtain detailed knowledge about the development situation (using a methodology) and make decisions about the applicable method.…”
Section: T H E O R Y O F I N F O R M a T I O N S Y S T E M S E N G I mentioning
confidence: 99%
“…Method engineering is the systematic discipline of designing, constructing and adapting ISD methods (Kumar & Welke, 1992), and is primarily focused on the relationship between methodologies and methods (Brinkkemper, 1995;Iivari et al, 2000). There is empirical evidence that method engineering has already had impact on methods, if informally, as existing research on method use in practice has consistently found that information systems methods, as far as they are used, are applied adaptively, customized to fit the organization and project in question without regard for the tools' consistency or appropriateness with the methodology involved (Wynekoop & Russo, 1993;Hardy et al, 1995;Chatzoglou & Macaulay, 1996;Fitzgerald, 1996). Situational method engineering assumes that the developer can obtain detailed knowledge about the development situation (using a methodology) and make decisions about the applicable method.…”
Section: T H E O R Y O F I N F O R M a T I O N S Y S T E M S E N G I mentioning
confidence: 99%
“…systems development, management consulting) have demonstrated large discrepancies between the formal models and observed actions. For example, studies of the use of formal models for software development have repeatedly shown that the models are not rigidly followed (Leonard-Barton, 1987;Hardy et al, 1995;Fitzgerald, 1996Fitzgerald, , 1997Fitzgerald, , 1998Sauer and Lau, 1997). In fact, several studies in the context of systems development even suggest that a rigid use of models may lead to less efficient development work (Hardy et al, 1995;Wastell, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…As a term, Methodology is often confused with methods and techniques. Although the suffixlogy suggests Methodology is the 'study of methods', the term is often used as a more grandiose term for methods (Fitzgerald 1996). Hence, the traditional SDLC methodology may apply the same interview methods as the object-oriented methodology, but they differ in concepts, beliefs and expectations (Sircar et al, 2001).…”
Section: Review Of Isd Framework Knowledgementioning
confidence: 99%
“…There are even signs of cumulative tradition in agile development (Fitzgerald 2006) and object-orientation (Agarwal et al, 1996; Burton-Jones and Meso 2006), which are also topics within the Methodology knowledge area. Advanced methodological issues such as the move away from formal and traditional methodologies (Naumann and Jenkins 1982;Fitzgerald 1996) and how methodologies are actually applied in practice (Fitzgerald 1997;Hardgrave et al, 2003) have also been extensively studied and demonstrate cumulative tradition.…”
Section: Review Of Isd Framework Knowledgementioning
confidence: 99%